“20 Lucas”: Discrimination and representation of andean People in the peruvian food phenomenon era - Yaranga Hernández, Mayra Rosario (2012)
This case study is a summary of the dissertation submitted to obtain my Master's Degree in Media, Culture and Identityfrom the University of Roehampton, London. This work explores and analyses a Peruvian television cookery programmecalled 20 Lucas, in which recognized Peruvian chefs are invited to cook a meal for four people using a budget of up to 20soles, so they have to go to popular markets and interact with the market sellers. The study has three main aims: to describehow Andean people are normally portrayed in Peruvian media, to decide whether the representation of local Andeanmarket traders in 20 Lucas remains similar to such representation, and to explore what the possible effects of 20 Lucas'portrayal of Andean people might be in Peruvian society in relation to the discrimination problem.The research was motivated by the possible lack of realistic representation on Peruvian television, which mostly serves as aplatform of exhibitionism and humiliation, and the resulting necessity for a better and more truthful representation ofordinary Peruvian people in the media